2021
DOI: 10.1029/2021gc009662
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Brittle Deformation at the Pāpaku Fault, Hikurangi Subduction Margin, NZ, IODP Expedition 375

Abstract: Quantifying fault damage zones provides a window into stress distribution and rheology around faults. International Ocean Discovery Program (IODP) Expeditions 372/375 drilled an active thrust splay fault within the Hikurangi subduction margin. The fault, which is hosted in Pleistocene clastic sediments, is surrounded by brittle fractures and faults as well as ductile deformation features. We find that fracture density in the damage zone enveloping the fault is asymmetric, with the hanging wall showing greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…Drilling-induced deformation should only affect material closest to biscuit boundaries, which were avoided during sampling, while hydrothermal fluids at this location are <100°C (Barnes et al, 2010;Cook et al, 2020), which is below what would be required for biomarker reaction here. Furthermore, we do not see a correlation between heating anomalies and fracture density (Savage et al, 2021), which we may expect if fluids or methane COFFEY ET AL. U  where reaction was not observed, the red dashed line indicates the minimum amount of reaction required to produce a thermal-maturity signal above background.…”
Section: Constraints On Possible Earthquake Displacementscontrasting
confidence: 68%
“…Drilling-induced deformation should only affect material closest to biscuit boundaries, which were avoided during sampling, while hydrothermal fluids at this location are <100°C (Barnes et al, 2010;Cook et al, 2020), which is below what would be required for biomarker reaction here. Furthermore, we do not see a correlation between heating anomalies and fracture density (Savage et al, 2021), which we may expect if fluids or methane COFFEY ET AL. U  where reaction was not observed, the red dashed line indicates the minimum amount of reaction required to produce a thermal-maturity signal above background.…”
Section: Constraints On Possible Earthquake Displacementscontrasting
confidence: 68%
“…The power indices of 0.52 and 0.73 for normal faults and strike-slip faults, respectively, are both less than 1, indicating that the development width of fault damage zones slows down with the continuous increase in fault displacement. Previous studies have shown that the threshold for this low displacement is approximately 2 × 10 3 m [50]. When the cumulative displacement is below this threshold, the rate of increase in the width of fault damage zones becomes more severe with the increase in displacement.…”
Section: Width Of the Fault Damage Zonesmentioning
confidence: 84%
“…where S i is the mean fracture frequency for each surveying site, D is the fracture frequency (m 3 ), x is the distance from the fault (km), a is a constant, and n is the decay parameter, which characterizes the degree of decay of the fracture frequency in the damage zones; a larger decay parameter indicates that the damage is attenuated more rapidly [50].…”
Section: Characterization Of Fracture and Strength Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations